Cable Laying and Pulling - Bolotinha, Manuel (Neutro à Terra, 2016)
The common methods of cable laying are: • Direct in the ground in trenches (underground cables). • In cable trenches in outdoors switchyards. • In cable trays or cable ducts • Fixed with clamps (usually at walls and ceilings). • In conduits.